EXPLORING SOCIO-POLITICAL VALUES IN THE HAJJ EXPERIENCE - Mastori Mastori; Indra Martian Permana; Paimun Paimun (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
As part of the fifth pillar of Islam, the obligation of Hajj is enthusiastically welcomed by Muslims from all corners of the world. Expensive costs and extra preparation do not stop Muslims from being able to worship and visit Baitullah. Apart from its position as a spiritual worship which is hablu minallah in nature, the Hajj pilgrimage has social and political dimensions which are important for Muslims to realize after the Hajj. This research method uses qualitative-descriptive methods. The type of data used is library data sourced from books, journals and news sites related to the Hajj pilgrimage. The research results show: first, spiritually the Hajj pilgrimage plays an important role in strengthening the theological relationship between a servant and Allah. Second, socially, worship has shared values ​​which are very relevant to the needs of modern society in creating social intimacy and da'wah. Third, politically, the Hajj pilgrimage has a strong aim to form the unity and unity of the Islamic world.